2014
DOI: 10.1007/s00221-014-3942-9
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory nausea in animal models: a review of potential novel therapeutic treatments

Abstract: Cancer patients undergoing chemotherapy continue to experience the debilitating side effect of nausea associated with their treatment. Although acute and delayed vomiting have become well managed with the advent of the 5-hydroxytryptamine-3 antagonists, such as ondansetron, and the neurokinin-1 receptor antagonists (such as aprepitant), nausea is still a relatively unmanaged adverse side effect of chemotherapy treatment. When nausea and vomiting are not properly managed, patients are at a greater risk of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 266 publications
2
10
0
Order By: Relevance
“…Once AN develops in such patients, the currently available antiemetic agents, e.g., the 5-HT 3 receptor antagonists, such as ondansetron, are completely ineffective (Morrow et al 1998a, b;Aapro et al 2005;Foubert and Vaessen 2005). Interestingly, such treatments are also ineffective in reducing the expression of contextually elicited conditioned gaping in rats (see Rock et al 2014 for review).…”
Section: Introductionmentioning
confidence: 96%
“…Once AN develops in such patients, the currently available antiemetic agents, e.g., the 5-HT 3 receptor antagonists, such as ondansetron, are completely ineffective (Morrow et al 1998a, b;Aapro et al 2005;Foubert and Vaessen 2005). Interestingly, such treatments are also ineffective in reducing the expression of contextually elicited conditioned gaping in rats (see Rock et al 2014 for review).…”
Section: Introductionmentioning
confidence: 96%
“…Chemotherapy treatment commonly causes distressing and debilitating side effects in cancer patients, including acute and delayed vomiting (Martin 1996); acute, delayed and anticipatory nausea (Rock et al 2014b); reduced food intake and bodyweight (Hainsworth and Hesketh 1992); and fatigue (Ahlberg et al 2003). These chemotherapy-induced nausea and vomiting (CINV) symptoms are highly distressing for patients, adversely affecting quality of life to the point where some will delay and even consider refusing future cycles of chemotherapy treatment (Janelsins et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete or ineffective control of nausea can cause increased anxiety, depression and the development of anticipatory nausea in patients (Rock et al 2014b). Anticipatory nausea (AN) manifests as nausea (sometimes accompanied by vomiting) prior to administration of chemotherapy, and occurs in up to 20 % of patients before any one chemotherapy cycle and in up to 30 % of patients by the fourth cycle (Roscoe et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conditioned gaping in rats requires similar orofacial musculature as vomiting in emetic species (Travers and Norgren, 1986) and is topographically similar to the orofacial components of retching in the shrew (Parker, 2003). These conditioned gaping reactions are not only displayed to nausea-paired flavours, but they are also displayed to nausea-paired contextual cues, serving as a model of anticipatory nausea experienced by patients receiving chemotherapy treatment upon their return to the clinic Rock et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Both FAAH and MAGL are distributed throughout the brain and periphery. The action of AEA, OEA and PEA can be prolonged by up to 24 h by pharmacological inhibition of their degradation by FAAH, and the action of 2-AG can be prolonged by up to 24 h by MAGL inhibition (Cravatt et al, 1996), providing effective strategies for reducing acute and anticipatory nausea as assessed by the rat gaping models (Rock et al, 2014;Sticht et al, 2015). Sticht et al (2016) demonstrated that elevation of 2-AG by MAGL inhibition in the interoceptive insular cortex (IIC), a cortical site responsible for the experience of nausea (Penfield and Faulk, 1955;Napadow et al, 2013), reduces nauseainduced conditioned gaping in rats.…”
Section: Introductionmentioning
confidence: 99%